2014
DOI: 10.1016/j.jterra.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Application of a hillslope-scale soil moisture data assimilation system to military trafficability assessment

Abstract: Soil moisture is an important environmental variable that impacts military operations and weapons systems. Accurate and timely forecasts of soil moisture at appropriate spatial scales, therefore, are important for mission planning. We present an application of a \ soil moisture data assimilation system to military trafficability assessment. The data assimilation system combines hillslope-scale (e.g., 10s to 100s of m) estimates of soil moisture from a hydrologic model with synthetic L-band microwave radar obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The US Army has been cooperating with other agencies to understand how satellitederived soil moisture can be incorporated into existing terrain characterization models (Baylot et al, 2013;Frankenstein et al, 2015). Flores et al (2014) demonstrated the usefulness of soil moisture data similar to that expected from the NASA Soil Moisture Active Passive (SMAP) mission. They simplified their analysis by considering only mobility limitations caused by soil strength, which, as Flores et al (2014) noted, may overemphasize soil strength impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The US Army has been cooperating with other agencies to understand how satellitederived soil moisture can be incorporated into existing terrain characterization models (Baylot et al, 2013;Frankenstein et al, 2015). Flores et al (2014) demonstrated the usefulness of soil moisture data similar to that expected from the NASA Soil Moisture Active Passive (SMAP) mission. They simplified their analysis by considering only mobility limitations caused by soil strength, which, as Flores et al (2014) noted, may overemphasize soil strength impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Flores et al (2014) demonstrated the usefulness of soil moisture data similar to that expected from the NASA Soil Moisture Active Passive (SMAP) mission. They simplified their analysis by considering only mobility limitations caused by soil strength, which, as Flores et al (2014) noted, may overemphasise soil strength impacts.…”
Section: Introductionmentioning
confidence: 87%
“…Flores et al (2014) demonstrated the usefulness of soil moisture data similar to that expected from the NASA Soil Moisture Active Passive (SMAP) mission. They simplified their analysis by considering only mobility limitations caused by soil strength, which, as Flores et al (2014) noted, may overemphasise soil strength impacts. Stevens et al (2016) employed a simplified time series approach based upon only soil moisture time series and compared mobility assessment using three different soil moisture sources.…”
Section: Introductionmentioning
confidence: 87%